Rare truncating variants in the sarcomeric protein titin associate with familial and early-onset atrial fibrillation. Issue 1 (December 2018) - Ahlberg, Gustav; Refsgaard, Lena; Lundegaard, Pia; Andreasen, Laura; Ranthe, Mattis; Linscheid, Nora; Nielsen, Jonas; Melbye, Mads; Haunsø, Stig; Sajadieh, Ahmad; Camp, Lu; Olesen, Søren-Peter; et al.
Abstract A family history of atrial fibrillation constitutes a substantial risk of developing the disease, however, the pathogenesis of this complex disease is poorly understood. We perform whole-exome sequencing on 24 families with at least three family members diagnosed with atrial fibrillation (AF) and find that titin-truncating variants (TTNtv) are significantly enriched in these patients (P  = 1.76 × 10−6 ). This finding is replicated in an independent cohort of early-onset lone AF patients (n  = 399; odds ratio = 36.8;P  = 4.13 × 10−6 ). A CRISPR/Cas9 modified zebrafish carrying a truncating variant of titin is used to investigate TTNtv effect in atrial development. We observe compromised assembly of the sarcomere in both atria and ventricle, longer PR interval, and heterozygous adult zebrafish have a higher degree of fibrosis in the atria, indicating that TTNtv are important risk factors for AF. This aligns with the early onset of the disease and adds an important dimension to the understanding of the molecular predisposition for AF. Common genetic variants in structural proteins contribute to risk of atrial fibrillation (AF). Here, using whole-exome sequencing, the authors identify rare truncating variants inTTN that associate with familial and early-onset AF and show defects in cardiac sarcomere assembly inttn.2 -mutant zebrafish.